The planning policy of bilingualism in education in Iraq - Yaseen, Bilal Huri; Shakir, Hani; T. Mansor, Tenku Mazuwana (Australian International Academic Centre, Australia, 2016)
Iraq as a multicultural and multilingual country has different languages as Arabic, which is the dominant language, and it also has some other minority languages, such as Kurdish, Turkish, Syriac....etc. Over the last 80 years, Iraq which was involved in some political struggles, had faced many internal problems regarding the Arabic domination that occurred, and this was owing to the absence of clear language policy used. Children learning in the Iraqi system, for instance, speak and study all courses in Arabic, while speaking and using their own culture at home tend to be done in their first language. The minorities’ language usage in Iraq was ignored both inside the schools as well as in the curriculum construction. So this study focuses on the following issues: the first issue is, What is the strategy of language planning policy in Iraq? the study discusses the strategy and the planning educational system that Iraq applies now, the second issue is, What is the status of minority languages in Iraq? Iraq is a multicultural county and has many minorities communities with different languages, the third issue is, What are the challenges of language in Iraq? as long as there is different languages within one country the study also focuses on the challenges that been faced in the planning policy system, and the last issue is, Is there a homogenous relationship during the current policy? How? the study shows the homogenous relationship inside the current policy and the researches give many suggestions and recommendations regarding to the current policy and what is needed for improving the educational planning policy system.